2023
DOI: 10.1002/anie.202300459
|View full text |Cite
|
Sign up to set email alerts
|

Porous Covalent Organic Framework Based Hydrogen‐Bond Nanotrap for the Precise Recognition and Separation of Gold

Abstract: Utilizing weak interactions to effectively recover and separate precious metals in solution is of great importance but the practice remains a challenge. Herein, we report a novel strategy to achieve precise recognition and separation of gold by regulating the hydrogen-bond (H-bond) nanotrap within the pore of covalent organic frameworks (COFs). It is found that both COF-HNU25 and COF-HNU26 can efficiently capture Au III with fast kinetics, high selectivity, and uptake capacity. In particular, the COF-HNU25 wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…The peak of N 1s at around 400.3 eV was assigned to the C−N bonds of the β-ketoamine linkages. 37 Field emission scanning electron microscopy (FE-SEM) confirmed the homogeneous rod-like crystallites of TPBD-R-COF with nanometer to micrometer sizes (Figures S6−S9 The porosities of all of the materials were determined by N 2 adsorption−desorption isotherms at 77 K. The type IV sorption isotherm plots revealed that each COF exhibited the mesoporous characteristics (Figure 2E). The Brunauer− Emmett−Teller specific surface areas of TPBD-H-COF, TPBD-F-COF, TPBD-CN-COF, and TPBD-NO 2 -COF were calculated to be 1005, 1492, 1073, and 335 m 2 /g, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 83%
“…The peak of N 1s at around 400.3 eV was assigned to the C−N bonds of the β-ketoamine linkages. 37 Field emission scanning electron microscopy (FE-SEM) confirmed the homogeneous rod-like crystallites of TPBD-R-COF with nanometer to micrometer sizes (Figures S6−S9 The porosities of all of the materials were determined by N 2 adsorption−desorption isotherms at 77 K. The type IV sorption isotherm plots revealed that each COF exhibited the mesoporous characteristics (Figure 2E). The Brunauer− Emmett−Teller specific surface areas of TPBD-H-COF, TPBD-F-COF, TPBD-CN-COF, and TPBD-NO 2 -COF were calculated to be 1005, 1492, 1073, and 335 m 2 /g, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 83%
“…The higher ζ-potential of PCN-224 in light led to relatively stronger repulsion to positive nonprecious metal ions, thus showing enhanced selectivity. In summary, we found that visible light largely promoted the Au recovery performance of PCN-224 and made it superior to other materials in terms of recovery capacity ( q max ) and selectivity ( K d ), including UiO-66, COFs, polymers, ,,, and 2D materials ,, (Figure S9).…”
Section: Resultsmentioning
confidence: 90%
“…[9] Specifically, several COFs with different functional groups were proposed to endow COFs with specific recognition and high uptakes for gold ions via H-bond interaction. [10] Most COFs for Au capture focused on modifying the porous walls with specified groups (e.g., thiol, phenolic and amide groups) to construct H-bond traps to capture Au. [11] However, the development of frameworks was ignored because of the weak binding ability of the Au ions.…”
Section: Introductionmentioning
confidence: 99%
“…Introducing binding groups along the pore walls of COFs has been shown to capture various ions such as Hg 2+ , UO 2 2+ , and Cr 4+ [9] . Specifically, several COFs with different functional groups were proposed to endow COFs with specific recognition and high uptakes for gold ions via H‐bond interaction [10] . Most COFs for Au capture focused on modifying the porous walls with specified groups (e.g., thiol, phenolic and amide groups) to construct H‐bond traps to capture Au [11] .…”
Section: Introductionmentioning
confidence: 99%